Positive Solutions for a Mixed-Order Three-Point Boundary Value Problem for p-Laplacian - Francisco J. Torres (Abstract and Applied Analysis)
The author investigates the existence and multiplicity of positive solutions for boundary value problem of fractional differential equation with p-Laplacian operator. The main tool is fixed point index theory and Leggett-Williams fixed point theorem.